Assessment of the Impact of Community-Based Tourism on the Economic, Social, and Cultural Empowerment of Women (Case Study: Coastal Villages of Bushehr Province) - Ali Shamsoddini; Fatemeh Dehghani (برنامه ریزی فضایی)
Abstract:The Achievement of sustainable rural development necessitates active participation of all stakeholders within these communities. Among the crucial components for progress and development in rural areas is the enhancement of manpower skills. Recognizing significant involvement of rural women in village production activities, growth of tourism in these regions presents a new opportunity for their engagement in development, thereby underscoring the importance of their empowerment. Empowerment has emerged as a fundamental aspect of sustainable development, wherein augmenting women's capacity and control over resources can be facilitated through tourism development. This research aimed to assess the role of community-based tourism in the economic, social, and cultural empowerment of women residing in the coastal villages of Bushehr Province. This study adopted a practical research approach with survey-based data collection. The research population comprised the residents of coastal villages in Bushehr Province. The sample size for this study was determined to be 400 individuals using Cochran’s formula. Statistical analysis, employing the one-sample T-test and utilizing AMOS and SPSS software, was conducted. The theoretical framework and the results of the statistical analysis employed in this research demonstrated the positive impact of tourism development on the economic, social, and cultural empowerment of women in the coastal villages of Bushehr Province. Keywords: Community-Based Tourism, Rural Development, Empowerment, Coastal Villages. Introduction:Social science experts emphasize that sustainable rural development cannot be achieved without the active participation of all stakeholders, particularly in the economic and social realms. Consequently, development of human resource skills emerges as a critical component for progress and growth in rural communities. Developed human resources can be regarded as an indispensable factor and prerequisite for attaining sustainable rural development.In line with the principle of equity in sustainable development, all beneficiaries, especially local residents, should have the opportunity to participate in decisions that affect their lives and enjoy the benefits of development. Given the active involvement of rural women in village production activities, emergence of tourism in these areas, and creation of new avenues for their participation in development, the significance of focusing on women's empowerment becomes increasingly apparent. Empowerment has now become a fundamental concern in the realm of sustainable development. As a service sector and a branch of sustainable development, tourism possesses the potential to empower communities.Empowerment primarily targets vulnerable groups in the society, who have experienced social exclusion, thus being deprived of full participation in a broader society through various means. Extensive studies indicate that women are considered a vulnerable and marginalized social group, often lacking control over resources and access to equal opportunities and positions. Research has demonstrated that the entire society benefits when women are supported and empowered.Development theorists view empowerment as an effective strategy for reducing gender inequalities in terms of capacities, resource access, opportunities, and a pathway to sustainable development. By enhancing women's power and control over resources, tourism development can play a crucial role in empowering women. Women's participation in tourism brings numerous benefits, including economic development in marginalized areas, sustainable utilization of natural resources, and heightened local control over development. Accordingly, this research aimed to evaluate the role of community-based tourism in the economic, social, and cultural empowerment of women residing in the coastal villages of Bushehr Province. Materials & Methods:This research was of an applied nature, employing a descriptive-analytical implementation method and utilizing survey-based data collection. The statistical population of this study consisted of residents living in the coastal villages of Bushehr Province. The sample size determined using Cochran's formula was 400 individuals. To analyze the data, both descriptive and inferential statistical methods were employed within the AMOS and SPSS software environment. The study area for this research encompassed 45 coastal villages within Bushehr Province. Research Findings:The literature highlights that tourism activities implemented with a community-based approach and local community participation bring about numerous economic and socio-cultural benefits to rural communities. Experts suggest that along with the establishment and expansion of this type of tourism, changes in social relations within the host society and transformations in social network connections can be anticipated. Ultimately, these developments contribute to the economic and social empowerment of rural residents. Table of standardized factor loadings and t-statistics between variablesVariable Components Standardized load factor Amount of tSignificance level Cronbach's alpha Rank Result Empowerment Economical 0.779--0,9521Optimal social 0.7126,129***2Optimal cultural 0,6215,102***3Optimal  The table above demonstrates that the t-statistics values for enablers and their components are significant, surpassing 1.96. Hence, it can be inferred that the enablers can be divided into three subsets or sub-components. Cronbach's alpha coefficient for the entire questionnaire is 0.952, exceeding the threshold of 0.7, indicating a favorable level of construct reliability. All criteria, including Cronbach's alpha and significance of factor loadings between the questions and underlying variables, confirm suitability of the measurement model. Discussion of Results & Conclusion:The theoretical framework of this research based on the sustainable development approach coupled with the findings derived from the statistical analysis revealed the positive impact of tourism development on the economic, social, and cultural empowerment of women residing in the coastal villages of Bushehr Province. These results signified that community-based tourism in the region had successfully generated women's interest in village development, fostering group activities, cooperation, and interpersonal interaction. Furthermore, it had improved public perception regarding women's contributions to the tourism sector, leading to their active participation in village public meetings, problem-solving endeavors, communal responsibilities, consensus-building, and consultations on village-related matters. Moreover, women had played a crucial role in safeguarding village tourism attractions, fostering empathy and unity, managing their own affairs, enhancing their understanding of village tourism issues, promoting local attractions to others, and encouraging acquisition of necessary skills for engaging in tourism activities. Ethical Considerations:All study participants provided informed consent and the researchers assured them of complete confidentiality and anonymity in relation to the study results. Authors' Contributions:All authors have made equal contributions to the study, including involvement in the study design, data analysis, interpretation, and final approval of the article. Conflicts of Interest:The authors declare no conflicts of interest.